PENGARUH EDUKASI PASAR MODAL TERHADAP PERSEPSI RISIKO DAN MINAT BERINVESTASI MASYARAKAT - Pratiwi Dewi (Fakultas Ekonomi, Program Studi Akuntansi, Universitas Warmadewa, 2020)
The majority of our society is not yet aware of the benefits of investing. They emphasize more importance to support life now without understanding the future. In Indonesia, based on data as of December 2018, only around 1,617,367 million were approved as independent shareholders in the Indonesian Central Securities Depository. The ratio is not even up to 0.5 percent of the total population of Indonesia. Market information and market knowledge are the main things. Today many countries agree to investment plans that want to increase domestic and international investment. This study aims to reveal the effect of capital market education on risk perceptions and community investment interests. Researchers want to look at the factors that influence the interest of investing in the community who incidentally do not have experience in investing in the stock market capital. This study uses primary data that is a questionnaire collected from participants, using a quasi-experimental technique in which participants are people who take part in voluntary capital market school activities at the Indonesian Stock Exchange KP Denpasar. The method of processing data uses path analysis. The results of this study capital market education has a positive influence on people's perceptions of interest and investment interest. While the perception does not have an interest in the interests of investing in the community.